Lagu Dolanan dalam Permainan Tradisional sebagai Strategi Inovasi Pendidikan Sendratasik - Bramantyo, Triyono; Tjaroko, Winarjo Sigro (Institut Seni Indonesia Yogyakarta, 2021)
Dolanan songs in traditional games as an innovation strategy for the art education of drama, dance, and music. This research focuses on constructing alternative learning in an innovation strategy of art education of drama, dance, and music through dolanan songs in traditional children's games. Alternative strategies are needed in providing diversification of learning because the problem that occurs in the art education of drama, dance, and music is the existence of cultural conflicts that impact the stagnation of the learning model. The choice of the dolanan song is due to its meaning and philosophy, which have aesthetic value in aspects of motion, drama, and music with the ability to adapt to the dynamics of science and technology. A library method is an approach used to construct an innovation strategy from the meaning contained in the text of children's traditional game songs. They implicitly have imaginative factors, particular messages, and aesthetic elements. Therefore, they can be relevant to the social conditions of society in the new cultural order. Based on the elaboration done in the study, three strategies are found which can answer the research problems, and are used in developing the art education of drama, dance, and music. They are as follows: firstly, the strategy of revitalizing the dolanan song in traditional children's games; secondly, the art education of drama, dance, and music is an appreciation education about aesthetic meaning; and thirdly, the formal transmission strategy of traditional transmission children's games through schools.